Drinking water quality, composition in the southwestern region of Tuv province (Bulletin of the Institute of Chemistry and Chemical Technology, 2022)
This research work was performed within the framework of the project titled “The survey on the drinking water quality of settlement areas of Tuv province, conclusion and recommendation” implemented at the Institute of Geography and Geoecology, MAS in 2021, and some of the research results are summarized in this article. We took totally 16 samples from the water supply wells at the center of 8 soums. Performed by physicochemical, micro-elements, and bacteriological analysis, and determined the chemical composition, quality and pollution parameters and the quality and composition. We determined the quality of underground water was evaluated by calculating the water quality index (WQI). As regards the anions, the first most prominent water types are the Ca-[HCO3] (50%), the second Х-[HCO3] (43.7%), the third Ca-[HCO3-SO4 2- ] (6.3%) and groundwater was dominated by mixed type of water. From the study results, in case of mineralization, groundwater at 50% surveyed locations belongs to fresh, 50% belongs to freshly or relatively high mineralization. In case of hardness, groundwater at 43.7% belongs to softish, 50% belongs to moderately hard and the remaining 6.3% to hard, respectively. According to the analysis of microelements, the uranium concentration (U 33-176 µg/l) was 1.1-5.86 times higher than the drinking water standard, strontium concentration (Sr 2021µg/l) was 21 μg/l more (1 out of 16), and nitrate concentration (NO3 63.0 mg/l) was 1.26 times more (1 out of 16) of the total groundwater samples. Total 11 samples collected from sampling points and the water supply wells covered by the survey does not meet the requirements of Drinking water. Hygienic requirements, and assessment of quality and safety MNS 0900:2018 standard by any or several parameters.Төв аймгийн баруун урд бүсийн ундны усны чанар, найрлагаХураангуй: Хүн ам баталгаат ундны ус хангамжийн үйлчилгээ хүртэж байгаа эсэхийг тогтоох зорилгоор ундны усны чанарын судалгааг аймаг тус бүрээр судалсан. Энэхүү судалгааны нэг болон 2021 онд хэрэгжсэн “Төв аймгийн төв, суурин газрын ундны усны чанарын судалгаа, дүгнэлт, зөвлөмж” гэрээт ажлын хүрээнд 27 сумын худаг уст, цэг хамрагдан физик, химийн үзүүлэлт болон бичил элемент, бактерлогийн шинжилгээг хийж химийн шинж чанар, найрлага, бохирдлыг тодорхойлсон судалгааны үр дүнгээс баруун урд бүсийн 8 сумын нутаг дэвсгэрээс нийт 16 худаг уст, цэгийн нарийвчилсан судалгааны үр дүнд боловсруулалт хийж, чанар найрлагыг тогтоон, газрын доорх усыг усны чанарын индекс (УЧИ-WQI)- ээр үнэлсэн. Судалгааны дүнгээс харахад тус судалгааны талбайд гидрохимийн шинж чанараараа 50% Ca-[HCO3], 45.81% Na-[HCO3], 12.51% Ca-[Mg]-HCO3, 43.7% холимог-[HCO3] найрлагатай ус тархсан байна. Судалгаанд хамрагдсан нийт уст цэгүүд нь эрдэсжилтийн хувьд цэнгэг болон цэнгэгдүү ангилалд хамаарч байгаа бол хатуулгийн хувьд маш зөөлөн, зөөлөн ус байхгүй, нийт уст цэгийн 43.7% нь зөөлөвтөр, 50% нь хатуувтар, 6.3% нь хатуу устай ангилалд тус тус хамаарч байна. Судалгаанд хамрагдсан уст цэгүүдээс 3 уст цэгт ураны (U 33-176 мкг/л) агууламж ундны усны стандартаас 1.1-5.86 дахин их, хүнцэл (As 36.7 мкг/л) 1 худгийн усанд 5.86 дахин их, стронций (Sr 2021 мкг/л) 1 худгийн усанд 21 мкг/л ээр их, нитратын ион ( NO3 - 63.0 мг/л) 1 уст цэгт 1.26 дахин их тус тус илэрсэн байна. Шинжилгээний дүнгээр нийт уст цэгийн 11 нь буюу 68.75% нь аль нэг юм уу хэд хэдэн үзүүлэлтээрээ “Хүрээлэн буй орчин, эрүүл мэндийг хамгаалах аюулгүй байдал. Ундны ус эрүүл ахуйн шаардлага, чанар, аюулгүй байдлын үнэлгээ” MNS 0900:2018 ундны усны стандартын шаардлага хангахгүй байна.Түлхүүр үг: газрын доорх ус, усны чанарын индекс, хатуулаг, хүнцэл, уран.